Complementary feeding practices and dietary intake among children 12-23 months in Mwingi district, Kenya. (5th March 2010) - Macharia-Mutie, Catherine W.; Brouwer, Inge D.; Mwangi, Alice M.; Kok, Frans J.
A cross-sectional study was carried out among 280 children (12-23 months), Mwingi district, Kenya. Complementary foods were introduced at age 2.5 ± 1.7 months and the mean duration of breastfeeding was 10.5 ± 4.1 months. An unfortified maize porridge was the main complementary food. At least 60% of the children in all the dietary diversity terciles consumed starchy staples and oils in the preceding 24 hr. The mean dietary diversity score was 4.9 ± 1.3 and 4.3 ± 1.0 out of a possible score of 14 and 8 as suggested by FAO, respectively. Dietary diversity was limited in animal products. Deficits in dietary energy, iron and zinc were found due to early introduction of complementary foods and low consumption of food rich in iron. Establishing local solutions to increase dietary diversity and promote use of foods rich in iron and proteins to improve available complementary diets are needed.